METODE PENDIDIKAN NABI MUHAMMAD SAW - Rusdiah Rusdiah (Al-Manba, 2026)
From the perspective of the Prophet Muhammad (peace be upon him), the learning method is an educational method carried out with wisdom and compassion, and adapted to the individual circumstances of the students. The Prophet (peace be upon him) employed various learning methods to ensure that the material presented was easy to understand and apply, and to foster noble character in both students and his companions. Some of the methods employed by the Prophet (peace be upon him) include exemplary behavior, habituation and repetition, practice or experimentation, and reward and punishment. The exemplary method involves providing examples of good behavior for students to emulate. The habituation and repetition method aims to form positive habits through continuous practice. The practice or experimentation method involves directly demonstrating the learning material to facilitate understanding. The reward and punishment method, on the other hand, is used to provide motivation, appreciation, and educational reprimands. The application of these methods demonstrates that the Prophet Muhammad (peace be upon him) was the best educator, capable of educating his people effectively and wisely. Therefore, the Prophet's learning methods are highly relevant for application in today's education system to develop students who are knowledgeable, have noble character, are disciplined, and responsible.